2018
DOI: 10.1111/mec.14870
|View full text |Cite
|
Sign up to set email alerts
|

How bacterioplankton community can go with cascade damming in the highly regulated Lancang–Mekong River Basin

Abstract: Rivers make vital contributions to the transport of water, sediment and nutrients from terrestrial to marine ecosystems. However, many large rivers worldwide are suffering from dam regulation. Increasing attention has been paid to bacterioplankton communities since they are highly responsive to river alterations and may influence biogeochemical processes. Here, a comprehensive study was conducted in the highly regulated Lancang-Mekong River Basin to address the question of how bacterioplankton communities resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 53 publications
6
24
0
Order By: Relevance
“…Taxonomic composition of microeukaryotes in the Lancang River are markedly different from those in estuaries (Chen et al., 2017) and oceans (Wu et al., 2017), probably due to the distinct differences in salinity and hydraulic conditions. Similar to the composition patterns of dominant bacterial phyla in rivers (Chen et al., 2020; Wang et al., 2018), the relative abundances of dominant microeukaryotic phyla varied between different river sections. Notably, Diatomea, as obligate phototrophs present in all types of aquatic ecosystems (Cermeno & Falkowski, 2009), had higher relative abundance in the upstream than in the downstream, for both planktonic and sedimentary microeukaryotes.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Taxonomic composition of microeukaryotes in the Lancang River are markedly different from those in estuaries (Chen et al., 2017) and oceans (Wu et al., 2017), probably due to the distinct differences in salinity and hydraulic conditions. Similar to the composition patterns of dominant bacterial phyla in rivers (Chen et al., 2020; Wang et al., 2018), the relative abundances of dominant microeukaryotic phyla varied between different river sections. Notably, Diatomea, as obligate phototrophs present in all types of aquatic ecosystems (Cermeno & Falkowski, 2009), had higher relative abundance in the upstream than in the downstream, for both planktonic and sedimentary microeukaryotes.…”
Section: Discussionsupporting
confidence: 65%
“…(2009) found that sedimentary bacteria in certain reaches of the Yellow River had slightly lower diversity than the bacterioplankton, presumably due to the high concentration of suspended sediment. Although bacterial diversity was reported to alter from headwaters to the river mouth (Savio et al., 2015; Wang et al., 2018), the change in microeukaryotic diversity in different river sections has rarely been investigated. For the planktonic microeukaryotic community, we observed lower species richness in the cascade reservoir section (from Mwei.A to NZD.4), especially in dam‐affected sites, suggesting a negative effect of dams on microeukaryotic diversity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that microbial diversity is significantly altered by varying geographical and environmental factors along a large river (Velimirov et al ., ; Tian et al ., ). Spatial variability of microbial composition from headwaters to the river mouth has been well demonstrated (Savio et al ., ; Chen et al ., ; Wang et al ., ), but most previous studies only focused on one taxonomic group. Regarding bacteria and fungi in large rivers, one would expect that the spatial patterns of their diversities differed substantially among different river sections.…”
Section: Discussionmentioning
confidence: 99%